2012
DOI: 10.1098/rspb.2011.2691
|View full text |Cite
|
Sign up to set email alerts
|

When should cuckolded males care for extra-pair offspring?

Abstract: In socially monogamous species with bi-parental care, males suffer reduced reproductive success if their mate engages in extra-pair copulations (EPCs). One might therefore expect that males should refuse to care for a brood if they can detect that an EPC has occurred. Here, we use a game-theory model to study male brood care in the face of EPCs in a cooperatively breeding species in which offspring help to raise their (half-) siblings in their parents' next breeding attempt. We show that under certain conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…). Paternal care for unrelated EPO has also been suggested to evolve if EPO help rear subsequent WPO (Liedtke and Fromhage ). Furthermore, male–male relatedness might also facilitate evolution of reproductive strategies involving leks and male coalitions (Shorey et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Paternal care for unrelated EPO has also been suggested to evolve if EPO help rear subsequent WPO (Liedtke and Fromhage ). Furthermore, male–male relatedness might also facilitate evolution of reproductive strategies involving leks and male coalitions (Shorey et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, helper contributions can increase with increasing relatedness (Griffin and West 2003;Nam et al 2010), and cooperative breeding is associated with low promiscuity (and hence high within-family relatedness) across species (Cornwallis et al 2010). Paternal care for unrelated EPO has also been suggested to evolve if EPO help rear subsequent WPO (Liedtke and Fromhage 2012). Furthermore, male-male relatedness might also facilitate evolution of reproductive strategies involving leks and male coalitions (Shorey et al 2000;Krakauer 2005;Hatchwell 2010a).…”
Section: Reproduction and Inbreedingmentioning
confidence: 99%
“…Although theories generally predict that males should invest more in the care of their genetic offspring and adjust their parental efforts to their share of paternity in the nest [12][13][14]61 , empirical supports have been mixed, with abundant exceptions where males do not seem to react to the loss of paternity by reducing their parental care efforts, such as in dunnocks 68,69 , reed buntings 70 , and western bluebirds 71 . Recent theoretical studies revealed some conditions where males may evolve to be insensitive to the loss of paternity, e.g., in cooperative breeding species where offspring help to raise their younger (half-)siblings 72 , or in the presence of male alternative reproductive tactics where the "sneaker" males specialize in gaining extra-pair paternity 73 . Empirical studies also found that in species where males were not sensitive to paternity loss, paternal care may not be costly in terms of parental survival 70 and/or the loss of opportunities for siring extra-pair offspring 37 .…”
Section: Uncertainty Of Paternity Selected Against Male Carementioning
confidence: 99%
“…Recent theoretical studies revealed some conditions where males may evolve to be insensitive to the loss of paternity, e.g. in cooperative breeding species where offspring help to raise their younger (half-)siblings [67], or in the presence of male alternative reproductive tactics where the "sneaker" males specialize in gaining extra-pair paternity [68]. Empirical studies also found that in species where males were not sensitive to paternity loss, paternal care may not be costly in terms of parental survival [30] and/or the loss of opportunities for siring extra-pair offspring [23].…”
Section: Uncertainty Of Paternity Selected Against Male Carementioning
confidence: 99%
“…Although theories generally predict that males should invest more in the care of their genetic offspring and adjust their parental efforts to their share of paternity in the nest [12][13][14]61 , empirical supports have been mixed, with abundant exceptions where males do not seem to react to the loss of paternity by reducing their parental care efforts, such as in dunnocks 68,69 , reed buntings 70 , and western bluebirds 71 . Recent theoretical studies revealed some conditions where males may evolve to be insensitive to the loss of paternity, e.g., in cooperative breeding species where offspring help to raise their younger (half-)siblings 72 , or in the presence of male alternative reproductive tactics where the "sneaker" males specialize in gaining extra-pair paternity 73 . Empirical studies also found that in species where males were not sensitive to paternity loss, paternal care may not be costly in terms of parental survival 70 and/or the loss of opportunities for siring extra-pair offspring 37 .…”
Section: Uncertainty Of Paternity Selected Against Male Carementioning
confidence: 99%